Monodisperse binary nanocomposite in silica with enhanced magnetization for magnetic separation - Yu, C; Lo, C; Tam, K; Tsang, S (2007)
The majority of research on magnetic nanoparticles has focused on optical, electrical, and magnetic storage areas. Recently, the application of magnetic nanoparticles as magnetically separable nanovehicles for chemical or biological species has become an area of intensive research but with rather different challenging criteria that are yet to be addressed. For example, the enhancement of intrinsically weak magnetic properties, avoidance of magnetic interactions among particles, and improvement of the stability of the nanoparticles remain key issues. Here, it is demonstrated using sequential nanochemistry preparation techniques that exchange-coupled nanomagnets, such as FePt-Fe 3Pt or FePt-Fe 3O 4 with dramatically enhanced magnetization, can be placed inside a silica nanosphere. The advantages of enhanced magnetization and the provision of protective coating and anchored sites on the silica shell surface render these new coated particles suitable for use in magnetic separation. © 2007 American Chemical Society.